2008
DOI: 10.1182/blood-2007-03-082024
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of apoptosis by and antitumor activity of lumiliximab in chronic lymphocytic leukemia cells and CD23+ lymphoma cell lines

Abstract: Lumiliximab is a chimeric macaquehuman monoclonal antibody to CD23, a protein expressed on virtually all chronic lymphocytic leukemia (CLL) cells. We examined the ability of lumiliximab to mediate apoptosis, antibody-dependent cellular cytotoxicity, and complementdependent cytotoxicity against primary CLL cells and CD23-expressing B-cell lines. Our data suggest that lumiliximab kills CLL cells and CD23-expressing B cells predominantly by apoptosis, which occurs through the intrinsic pathway.Lumiliximab-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…This type of treatment leads to B-cell apoptosis, further supporting a role for CD23 in CLL B-cell survival. 44 The self-activating loop of the responding CLL B cells might therefore be a powerful target for therapy in patients who present a Log-rank test was used to compare statistical differences in PFS and survival between both groups (P values are indicated).…”
Section: Discussionmentioning
confidence: 99%
“…This type of treatment leads to B-cell apoptosis, further supporting a role for CD23 in CLL B-cell survival. 44 The self-activating loop of the responding CLL B cells might therefore be a powerful target for therapy in patients who present a Log-rank test was used to compare statistical differences in PFS and survival between both groups (P values are indicated).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Lumiliximab induces similar levels of apoptosis to rituximab in CD23-bearing lymphoid cell lines and CLL cells after secondary cross-linking, and prolongs survival of severe combined immune deficiency mice inoculated with CD23-bearing lymphoblastic cell lines. 20 In preclinical studies, lumiliximab was shown to enhance the effects of fludarabine and rituximab, providing a rationale for combining lumiliximab with regimens containing fludarabine and rituximab in clinical trials in CLL. 20 As CD23 is expressed on a high proportion of CLL cells but is only minimally expressed on other cells, targeting this molecule provides a treatment modality that is specific to CLL with the potential to minimize additional toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…20 In preclinical studies, lumiliximab was shown to enhance the effects of fludarabine and rituximab, providing a rationale for combining lumiliximab with regimens containing fludarabine and rituximab in clinical trials in CLL. 20 As CD23 is expressed on a high proportion of CLL cells but is only minimally expressed on other cells, targeting this molecule provides a treatment modality that is specific to CLL with the potential to minimize additional toxicity. In a 46-patient, phase 1, doseescalation trial performed in patients with relapsed and refractory CLL, lumiliximab monotherapy was well tolerated at doses of up to 500 mg/m 2 given 3 times per week for 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Lumiliximab induces cell death in primary CLL cells mainly through apoptosis and does not show appreciable complement-dependent cytotoxicity or antibody-dependent cell-mediated cytotoxicity (ADCC) activity toward CLL cells. 39 Lumiliximab induces apoptosis through the downregulation of antiapoptotic proteins Bcl-2, Bcl-X L and X-linked inhibitor of apoptosis protein (XIAP), the activation of proapoptotic protein Bax and the release of cytochrome c. 39 In a phase I/II trial in patients with relapsed/refractory CLL, lumiliximab in combination with FCR produced an ORR of 71% (CR 48%, PR 10% and unconfirmed PR 13%), and it did not seem to increase the toxicity of the FCR regimen. 40 Compared with historical data on FCR alone, 41 the CR rate achieved with lumiliximab plus FCR appears to be higher.…”
Section: Lumiliximabmentioning
confidence: 99%